DIGITAL TWINS IN SMART CITIES: A CONCEPTUAL FRAMEWORK FOR URBAN PLANNING AND SUSTAINABILITY - Singh, Poonam (COMPUSOFT: An International Journal of Advanced Computer Technology, 2023)
Digital Twins, virtual representations of physical entities, are rapidly becoming integral to the development of smart cities. This paper proposes a conceptual framework for the application of Digital Twins in urban planning and sustainability efforts. The framework outlines how Digital Twins can be utilized to simulate, monitor, and optimize urban infrastructures, thereby enhancing city management and sustainability. By integrating various data sources, from IoT devices to environmental sensors, the framework aims to create a comprehensive digital mirror of the city that supports decision-making processes. This paper serves as a guide for urban planners, policymakers, and technologists interested in leveraging Digital Twins for smart city development.